C-reactive protein as a prognostic factor in cancer - Lorton, Cliona Mary (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2022)
Prognostication, the prediction of future outcomes, is a key aspect of cancer care but remains imprecise. An elevated serum C-reactive protein (CRP) is associated with high symptom burden, poor quality of life and shorter survival in cancer. CRP is inexpensive, widely available and straightforward to measure, making it an appealing potential prognostic marker. This thesis assessed promising, clinically relevant applications of CRP as a predictor of important patient outcomes in cancer, with a focus on oesophageal adenocarcinoma (OAC) and lung cancer. As a non-specific inflammatory marker, transient CRP elevations could cause inaccurate prognostication. CRP change over time (CRP kinetics) was assessed in mixed cancer and OAC cohorts. It was no better than standard prognostic markers at predicting survival but could have a role in other cancer cohorts. Numerous prognostic scores incorporate CRP, and a wide range of threshold (cutpoint) values for CRP have been reported in OAC. A systematic review and meta-analysis found inadequate evidence to conclude the best CRP cutpoint in OAC. Evidence was strongest for the Glasgow Prognostic Score (GPS) / modified GPS; future studies should focus on these scores. Presence of CRP within tumour tissue has been associated with shorter survival in several cancer types. In this thesis, tumoural CRP was demonstrated in pre- and post-treatment OAC tissue, predominantly in the stroma. A possible association with reduced survival was identified. Tumoural CRP was not correlated with serum CRP and an OAC cell line did not secrete CRP. Taken together, the results suggest a stromal origin for tumoural CRP in OAC. Elevated CRP and CT-assessed abnormalities of skeletal muscle are associated with, and may predict, poor quality of life (QoL) and high symptom burden in cancer. A feasibility study found several barriers to a definitive study of this relationship. Novel findings of associations between skeletal muscle measures (muscle density and psoas muscle index), CRP and patient outcomes (post-operative complications, symptoms and study non-completion) were identified. This thesis confirmed that CRP can be applied in novel ways and used in combination with other factors, to predict important clinical outcomes in cancer. It also demonstrated the value of robust prognostic factor research and highlighted the areas which should be examined in future work, to translate this promising prognostic factor into improved patient care.
APPROVED
Keywords: C-reactive protein; Cancer; Prognostic factor